PEMANFAATAN FUNGI Aspergillus flavus, Aspergillus terreus DAN Trichoderma harzianum UNTUK MENINGKATKAN PERTUMBUHAN BIBIT Rhizophora mucronata Lamk - Darmanto Ambarita; Yunasfi Yunasfi; Miswar Budi Mulya (Program studi Kehutanan USU, 2015)
Mangrove condition deteriorating lead to the quality and quantity of mangrove seedlings wane. To improve and get better mangrove seedlings, then the required rehabilitation of mangroves. One of the efforts is the use of various types of fungi that can enhance the growth of mangroves for the better. This research can provide information on the types of fungi are able to increase growth of seedling R mucronata. This study was conducted from June 2014 until January 2015 using a completely randomized design (CRD) with treatment application types of fungi and five replications. There are three types of fungi namely A. flavus applied, A.terreus T. harzianum. Application of Trichoderma harzianum gave the best results on seedling growth parameters R. mucronata, with an average height of 15.48 cm, a diameter of 0.47 cm, 1375.43 cm2 leaf area, and total dry weight of 119.50 g higher than the average of control and another fungi.Keywords: Rhizophora mucronata, Fungi, Mangrove, Rehabilitation.